PHARMACIST-LED INTERVENTIONS TO PREVENT OPIOID MISUSE - PATEL AYUSHI SHAILESHBHAI,; MEHTA HIRALBEN SATISHCHANDRA, (The Bioscan, 2025)
The opioid epidemic continues to be a major public health challenge worldwide, characterized by escalating rates of misuse, dependency, and overdose-related mortality. Pharmacists, as accessible and highly trusted healthcare professionals, are strategically positioned to play a pivotal role in mitigating opioid misuse and its associated consequences. However, pharmacists face several challenges in implementing these interventions effectively. Regulatory barriers, such as restrictions on prescribing naloxone or providing medication-assisted treatment, can limit their scope of practice. Resource limitations, including insufficient funding and lack of access to advanced tools like Prescription Drug Monitoring Programs (PDMPs), further hinder their efforts. Additionally, inadequate specialized training in opioid safety and stigma associated with harm reduction measures remain significant obstacles. Looking ahead, expanded pharmacist training programs and integration into multidisciplinary teams could enhance their impact. Digital health technologies, including telepharmacy and advanced PDMP tools, offer promising avenues to streamline efforts. Furthermore, fostering collaboration with public health organizations and policymakers can help pharmacists secure the resources and authority necessary to implement these strategies at scale. This Article will also showcase case studies and examples of successful pharmacist-led interventions to provide practical insights into overcoming these challenges and achieving measurable outcomes in opioid misuse prevention.